Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fnins.2019.00237
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Neurochemical Modulation by DZNep and GSK-J1: Potential Link With Histone Methylation Status

Abstract: Histone methylation/demethylation plays an important modulatory role in chromatin restructuring, RNA transcription and is essential for controlling a plethora of biological processes. Due to many human diseases have been related to histone methylation/demethylation, several compounds such as 3-deazaneplanocin A (DZNep) or 3-((6-(4,5-Dihydro-1H-benzo[d]azepin-3(2H)-yl)-2-(pyridin-2-yl)pyrimidin-4-yl)amino)propanoic acid; N-[2-(2-pyridinyl)-6-(1,2,4,5-tetrahydro-3H-3-benzazepin-3-yl)-4-pyrimidinyl]-β-Alanine (GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…In this regard, several reports have suggested an equilibration period of the microdialysis probes of >10 h before beginning the sample collection for obtaining reliable measurements (Hammarlund‐Udenaes, 2017; Leenaars et al, 2018; Murillo‐Rodriguez et al, 2004). In the current report, the microdialysis probes were stabilized for 24 h, and samples were collected as previously reported (Hambrecht‐Wiedbusch et al, 2014; Murillo‐Rodríguez et al, 2018, 2019, 2020; Schäble et al, 2011). During the whole microdialysis experiments, water and standard chow pellets (Purina, México) were available ad libitum for all rats.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, several reports have suggested an equilibration period of the microdialysis probes of >10 h before beginning the sample collection for obtaining reliable measurements (Hammarlund‐Udenaes, 2017; Leenaars et al, 2018; Murillo‐Rodriguez et al, 2004). In the current report, the microdialysis probes were stabilized for 24 h, and samples were collected as previously reported (Hambrecht‐Wiedbusch et al, 2014; Murillo‐Rodríguez et al, 2018, 2019, 2020; Schäble et al, 2011). During the whole microdialysis experiments, water and standard chow pellets (Purina, México) were available ad libitum for all rats.…”
Section: Methodsmentioning
confidence: 99%
“…The total estimation of ACh contents was determined by adding the concentration values from all collected samples taken during four continuous hours. The HPLC procedure for separation, detection and measurement of ACh was achieved as previously reported (Murillo‐Rodríguez et al, 2018, 2019, 2020). To avoid experimental bias, a laboratory member that analysed the samples was not aware of the identity of the individual dialysates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, studies have suggested that compounds such as 3deazaneplanocin A (DZNep) inhibit histone trimethylation of lysine 27 on histone H3 and lysine 20 on histone H4. DZNep is shown to control the sleep-wake cycle and release sleep-related neurochemicals via the histone methylation process [93].…”
Section: Histone Modificationmentioning
confidence: 99%